ANALYSIS OF THE COMPETITIVENESS OF CHINESE LIPSTICK IMPORTS BASED ON INDONESIAN CONSUMER DEMAND AND IMPORT DUTIES - Helni Febri Sentari; Ayuningtyas Yuli Hapsari (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the impact of Indonesian consumer demand for imported lipstick and import tariffs on the competitiveness of Chinese-made lipstick imports in Indonesia during the period 2015–2025. The phenomenon of rising cosmetics consumption, particularly lipstick, as well as China’s status as one of the primary suppliers of imported lipstick products to Indonesia, underscores the need for an analysis of the factors influencing the competitiveness of these imports. This study employs a quantitative method using multiple linear regression analysis. The results indicate that Indonesian consumer spending has a positive and significant effect on the competitiveness of imported Chinese lipstick products, whereas import tariffs have a negative but insignificant effect on the competitiveness of Chinese lipstick imports in Indonesia.